The use of DigComp in teaching and learning strategies: a roadmap towards inclusion - Balula, Ana (2016)
Nowadays, the development of digital competence is seen as crucial in the international scenario, especially in what concerns education, training, employment and lifelong learning. Thus, the main goal of this study is to identify research works that provide evidence of the use of DigComp Framework (put forward in 2013 and reviewed in 2016 by the European Commission Joint Research Center – Institute for Prospective Technological Studies) as theoretical basis for the design of teaching/learning strategies to develop digital competence, in particular as to problem solving. Consequently, this paper puts forward the results of an exploratory literature review, focussed on the open access studies (published between 2013 and 2016), in which teaching and learning strategies, grounded on DigComp Framework, are outlined. In general, results of the content analysis suggest that DigComp is primarily used for digital competence assessment and evaluation, and none of the selected works conveys examples on how digital competence development can be enhanced in concrete teaching and learning scenarios.